Our Hope - Heyana, Owam (Open Mic: A Creative Writing Journal, 2024)
Stanza Introduction: The drain has burst, the water has flooded our roads and the municipality hasn’t come to fix it. Our cars have found way into potholes so deep they could bury us. We watch cars getting hijacked and clutch our purses to our chests.